L2 Morphology Acquisition Perspectives in Optimality Theory: Preliminary Observations of The Case of the Acquisition of the Past Tense Marker “-ed” - Fehmi, Youssef (Journal of Humanities & Social Sciences, 2025)
L2 acquisition is currently an important issue in psycholinguistics research. The conception of grammar acquisition in L2 within the optimality paradigm is different from the Universal Grammar (UG) framework. Grammar consists of a set of innate universal constraints rather than a set of rules. These constraints account for all possible child’s input during the acquisition process. The function GEN (Generator) produces an infinite number of possible candidates. The learner based on his algorithm, which serves as a filter, will outrank optimal candidates in the hierarchy of constraints and demote the least optimal “the losers”. The child is able to outrank and demote candidates according to the evidence he gets from the input. The following study investigated morphology acquisition within the scope of the Optimality Theory. It aimed at examining the hypothesis of the emergence of the unmarked and the access to UG. The outcome of the study reveals that lower constraints remain in the grammar of the child and show up in cases of the emergence of the unmarked phenomena as indicated in the data recorded from my informant. Moreover, it was noticed that she still has access to the Universal Grammar (UG) since the general pattern of her utterances is characterized by a noticeable inclination towards unmarked forms rather than marked forms especially in the early stages of L2 acquisition.
Keywords: L2 acquisition; Universal Grammar; emergence of the unmarked; Optimality Theory (OT); morphology; Generator; markedness; faithfulness; constraints; ranking; input; output